REFORMULASI SANKSI PELAKU PENGANIAYAAN TERHADAP HEWAN DALAM KITAB UNDANG-UNDANG HUKUM PIDANA NASIONAL DIKAITKAN DENGAN TUJUAN PIDANA - Leonardo Sormin; Erdianto Erdianto; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Humans and animals were created to coexist and complement each other.But in Indonesia there are often acts of animal abuse. In Indonesia, legalarrangements related to animal abuse have been regulated in articles 336-338 ofthe National Criminal Code (KUHP). However, existing sanctions in Indonesiaare still not ideal in their application, so there are still many perpetrators ofanimal abuse. The purpose of this study is to identify ideal sanctions that shouldbe applied in Indonesia in the context of criminal purposes.This research is a normative legal research, it is based on literatureresearch that takes quotations from reading books or supporting books related tothe problem under study. This study used secondary data sources consisting ofprimary, secondary, and tertiary legal materials. This study also used qualitativedata analysis and produced descriptive data.From the results of the discussion and research conducted, it is necessaryto review the sanctions for animal abuse in the Criminal Code in Indonesia. Thisis because the current sanctions are not aligned with the purpose of punishmentwhich should provide a deterrent effect and coaching opportunities to theperpetrators of these crimes. In addition to the imposition of sanctions, additionalsanctions are also needed, such as a ban on animal ownership, animal-relatedsocial work, education and counseling, and monitoring and supervision.Keywords : Criminal Act, Persecution Animal, Purpose of Punishment